Preparation method and application of metal-free high-temperature ferromagnetic material and device
By inserting organic radical molecules between the two-dimensional material layers of graphene or transition metal disulfide, carriers mediate magnetic center exchange interactions, the stability and magnetic inadequacy of metal-free high-temperature ferromagnetic materials are solved. It achieves high Curie temperature and strong magnetism, suitable for the development of spintronics and quantum information processing devices.
Patent Information
- Application Number
- CN202411285632.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing organic/molecular magnets based on light elements are unstable in air environments at room temperature and normal pressure, the distance between the magnetic spin centers is long and the magnetic exchange effect is weak, resulting in the limited development of magnetic materials and the lack of high magnetic order temperatures. and strongly magnetized metal-free ferromagnetic materials.
Through electrochemical intercalation method, two-dimensional materials for inserting organic radical molecules such as pyridine, 7,7,8,8-tetracyanoterephthalene dimethane, naphthoquinone, etc. into graphene or transition metal disulfides, through electrochemical intercalation method, are used to insert organic radical molecules such as pyridine, 7,7,8,8-tetracyanoterephthalene dimethane, naphthoquinone, etc. into graphene or transition metal disulfides. High-temperature ferromagnetic materials are formed between layers, and carriers in two-dimensional materials mediate exchange interactions between magnetic centers.
The preparation of high-temperature ferromagnetic materials has been realized, with high Curie temperature, strong magnetism and environmental stability. It is suitable for the development of spintronics and quantum information processing devices, and the preparation method is green and simple, and the cost is low.
Smart Images

Figure CN119143124A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of two-dimensional high-temperature ferromagnets, and in particular to a preparation method and application of metal-free high-temperature ferromagnetic materials and devices. Background Art
[0002] Organic / molecular magnets are a class of paramagnetic materials. Compared with traditional metal-based magnetic materials, organic / molecular magnets have unique mechanical and functional advantages, including low density, optical transparency, high flexibility, low-temperature synthesis and processing, atomic-level controllability and sustainability. These practical properties have developed many potential applications, such as high-density data storage, quantum computing, magneto-optical switches, spin electronics and nanomedical devices. However, although molecular magnets based on light elements have very good development prospects, there are two factors that seriously limit the construction of ferromagnetic organic / molecular magnets based on light elements. First, they are unstable under air conditions at room temperature and pressure (for example, they are sensitive to humidity and temperature, etc.), and second, the distance between the spin centers of their magnetic aggregates is far and the magnetic exchange interaction between them is weak, which leads to great restrictions on the development of magnets in molecular free radical aggregate materials.
[0003] In the reports so far, most materials based on molecular magnets or nanoscale aggregates do not show a high magnetic ordering temperature or high magnetic properties. The essence is that, unlike the short-range exchange interaction (usually chemical bonds) between metal spin centers in inorganic magnets, the distance between adjacent spin centers in molecular radical materials is very long, resulting in relatively weak magnetic coupling interactions in their condensed structures. Therefore, finding a metal-free ferromagnetic material with long-range magnetic order, strong long-range coupling, strong magnetization, environmental stability and high Curie temperature is an urgent development direction in the field. Among them, the anomalous Hall effect is often considered to be one of the basic tests of quantum spin devices. This phenomenon reveals important information about the coupling between the microscopic spin motion and magnetic moment of electrons inside the material by measuring the change in the conductivity of the material under an external magnetic field. This testing method not only provides an effective means for studying the electromagnetic transport properties of new materials, but also has potential application prospects in the development of advanced quantum information processing devices.
[0004] Two-dimensional materials such as graphene provide a platform for exchange between magnetic spin centers. The indirect exchange interaction between two magnetic centers is likely mediated by itinerant electrons within the two-dimensional base plane. Although this theory is still based on calculations and has not been fully confirmed by experiments, it shows that the use of two-dimensional materials with high carrier mobility such as graphene can effectively promote exchange interactions between spin centers in molecular magnets. In addition, their interaction with two-dimensional materials can also provide a viable solution to the inherent instability problem that has always accompanied organic free radicals, and can solve all the fundamental challenges of building molecular-based ferromagnetic materials. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a metal-free high-temperature ferromagnetic material in view of the deficiencies in the prior art.
[0006] The technical problem that the present invention needs to solve is to provide a preparation method and application of the above-mentioned high-temperature ferromagnetic material.
[0007] In a specific application, the present invention also proposes the application and method of the above-mentioned high-temperature ferromagnetic material in the preparation of magnetic devices.
[0008] In order to solve the above technical problems, the present invention discloses a metal-free high-temperature ferromagnetic material, wherein the high-temperature magnetic material is obtained by inserting organic free radical molecules into the interlayer of a two-dimensional material by an electrochemical intercalation method, wherein the organic free radical molecules are any one or more of pyridine, 7,7,8,8-tetracyanoquinone dimethane (TCNQ), naphthoquinone (NTO), and hydroquinone, wherein the two-dimensional material is graphene or a transition metal disulfide represented by molybdenum disulfide.
[0009] The present invention also proposes a method for preparing the above-mentioned metal-free high-temperature ferromagnetic material, comprising the following steps:
[0010] A100: Dissolve certain organic free radical molecules in a solvent and dissolve them by ultrasonic to obtain a molecular organic solution;
[0011] A200: clamping a sheet-like block of two-dimensional material with a clamp, specifically clamping in a thickness direction of the two-dimensional material;
[0012] A300: partially immersing the clamped sheet-like bulk two-dimensional material in the molecular organic solution, and connecting the two-dimensional material and a suitable counter electrode respectively with two electrodes;
[0013] A400: Electrochemically intercalate the two materials for a certain period of time using a suitable constant voltage to obtain a two-dimensional molecular orbital coupled magnetic material, i.e., a high-temperature ferromagnetic material.
[0014] Specifically, in step A100, the solvent is any one of dimethyl sulfoxide, dimethylformamide, isopropanol, cyclohexane, acetone, and acetonitrile; and the molecular concentration range of the molecular organic solution is 5 mg / mL to 20 mg / mL.
[0015] In step A200, the thickness of the sheet-like block two-dimensional material ranges from 0.1 mm to 0.5 mm, the length and width range from 2 cm to 4 cm, and the area ranges from 2 cm 2 ~8cm 2 .
[0016] In step A400, the conditions for electrochemical intercalation are: a constant voltage range of -5V to -20V, a reaction time of 10min to 1h, and after the reaction is completed, the two-dimensional material is taken out and dried naturally.
[0017] The invention further discloses the application of high temperature ferromagnetic materials in the preparation of devices.
[0018] The present invention also proposes a magnetic device, which includes a substrate silicon wafer, a titanium eight-claw electrode, the above-mentioned high-temperature ferromagnetic material and an aluminum-silicon alloy wire, wherein the substrate silicon wafer has an oxide layer, the high-temperature ferromagnetic material is transferred to the oxide layer by hand tearing, the titanium eight-claw electrode is evaporated and attached to the high-temperature ferromagnetic material and the substrate silicon wafer to form a Hall device, and the aluminum-silicon alloy wire is used to connect the titanium eight-claw electrode to an external circuit.
[0019] Wherein, the oxide layer is silicon oxide, and the external circuit includes a digital source meter.
[0020] In one embodiment, the substrate silicon wafer is a square with a side length of 2.5 cm; the length of the aluminum-silicon alloy wire is 1-3 cm.
[0021] The present invention also discloses a method for preparing the magnetic device, comprising the following steps:
[0022] (1) Preparing a silicon wafer containing an oxide layer into a silicon wafer with eight-prong electrodes attached thereto: masking an eight-prong electrode pattern on the silicon wafer containing an oxide layer by ultraviolet lithography, and sequentially evaporating metal titanium and metal gold on the silicon wafer by electron beam evaporation, wherein the metal titanium serves as an adhesion layer and the metal gold serves as an electrode material; soaking the evaporated silicon wafer in acetone and ultrasonically treating it to remove the metal layer outside the eight-prong electrode area, and successively rinsing the silicon wafer with the eight-prong electrodes with acetone and isopropanol, and drying it with high-purity nitrogen to obtain a silicon wafer with eight-prong electrodes attached thereto;
[0023] (2) Transferring a two-dimensional material of appropriate thickness to a suitable position on a silicon wafer by a blue tape (UltraType) mechanical peeling method, specifically including:
[0024] The silicon wafer with the eight-claw electrode obtained in step S100 is placed in a plasma generator and cleaned with oxygen plasma, and then heated;
[0025] The two-dimensional material is torn into appropriate thickness by using blue tape (UltraType), and then transferred to the polydimethylsiloxane film (PDMS). Then, the two-dimensional material sample is transferred from the PDMS to the appropriate position of the silicon wafer using a transfer platform;
[0026] (3) Spin-coating polymethyl methacrylate (PMMA) on the silicon wafer obtained in step (2) by a spin coater, heating for a period of time, exposing a suitable single electrode pattern on the silicon wafer by an electron beam exposure process, and evaporating metal titanium and metal gold on the silicon wafer by electron beam evaporation;
[0027] (4) The evaporated silicon wafer obtained in step (3) is immersed in acetone and ultrasonically treated to remove the metal layer outside the octagonal electrode area, and a suitable window is exposed near the sample by an electron beam exposure process. An electrochemical three-electrode system is used, a carbon rod is used as a counter electrode, and Ag / AgCl is used as a reference electrode. An electrochemical intercalation reaction is performed in a reaction chamber prepared by PDMS material; wherein the solution is prepared under the conditions in the preparation method of high-temperature ferromagnetic materials.
[0028] (5) soaking the silicon wafer after the intercalation in step (4) in acetone to remove the extra PMMA, then re-spin-coating PMMA using a spin coater, heating at a suitable temperature, exposing an extra Hall electrode pattern on the silicon wafer using an electron beam exposure process, and evaporating metal titanium and metal gold on the silicon wafer using electron beam evaporation;
[0029] (6) The evaporated silicon wafer obtained in step (5) is placed in acetone and soaked to remove the extra PMMA, thereby obtaining a magnetic device based on metal-free high-temperature ferromagnetic material.
[0030] The present invention also proposes the application of the magnetic device in negative magnetic resistance and anomalous Hall.
[0031] Beneficial effects: Compared with the prior art, this application has the following advantages:
[0032] (1) Organic-inorganic intercalation material system based on organic molecules and two-dimensional materials. The present invention realizes a series of metal-free molecular intercalation material systems with high magnetism and high Curie temperature by changing the molecular / two-dimensional materials; realizes a material synthesis method to control the magnetic difference by changing the carrier concentration of the molecular / two-dimensional material system, which extends the new development of organic / metal-free spintronic devices and magnetoresistive devices;
[0033] (2) The synthesis method of two-dimensional molecular orbital coupled magnetic materials (i.e., high-temperature ferromagnetic materials) is green and simple, the preparation of magnetic devices is simple, the cost is low, and it has certain economic value and mass production value;
[0034] (3) A series of 2D molecular orbital coupled magnetic materials of different molecules / 2D materials can be synthesized, and material systems with different magnetic properties can be prepared for different application scenarios;
[0035] (4) The magnetic device of the present invention belongs to the field of spin electronics and proposes new extensions for negative magnetoresistance effect and anomalous Hall effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of molecular electrochemical intercalation based on metal-free high-temperature ferromagnetic materials in an embodiment of the present invention, wherein a is an overall electrochemical intercalation circuit and device diagram, b is a clamping method and immersion area of a sheet-like bulk two-dimensional material, and c is a material change before and after electrochemical intercalation;
[0037] Figure 2 Schematic diagram of a magnetic device based on metal-free high-temperature ferromagnetic material in an embodiment of the present invention;
[0038] Figure 3 The magnetic properties and comparison diagram of the metal-free high-temperature ferromagnetic material in the embodiment of the present invention;
[0039] Figure 4 Magnetic properties diagram of four molecules and two two-dimensional materials based on metal-free ferromagnets in the embodiments of the present invention;
[0040] Figure 5 Graph showing negative magnetoresistance and anomalous Hall properties based on metal-free high-temperature ferromagnetic materials in an embodiment of the present invention. DETAILED DESCRIPTION
[0041] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0042] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0043] Please refer to Figure 1 The present invention provides a method for preparing a metal-free high-temperature ferromagnetic material, the steps comprising:
[0044] A100: Dissolve a certain amount of molecules in a solvent, which is one of dimethyl sulfoxide, dimethylformamide, isopropanol, cyclohexane, acetone, and acetonitrile, and dissolve by ultrasonication to obtain a molecular organic solution;
[0045] A200: Cut the sheet-like block of two-dimensional material of appropriate thickness into appropriate size and clamp it with a suitable non-metallic electrode clamp;
[0046] A300: Part of the clamped sheet-like bulk 2D material is immersed in a molecular organic solution, and two electrodes are used to connect the 2D material and a suitable counter electrode respectively;
[0047] A400: Electrochemically intercalate the two materials for a certain period of time using a suitable constant voltage to obtain a two-dimensional molecular orbital coupled magnetic material.
[0048] The present application is described below through specific embodiments.
[0049] Example 1 Preparation of high-temperature ferromagnetic materials of graphene-pyridine system.
[0050] 50 mg of pyridine molecules were dissolved in 10 mL of dimethyl sulfoxide and dissolved by ultrasound for 5 minutes to obtain a molecular solution with a concentration of 5 mg / mL. A sheet of graphene material with a thickness of 0.1 mm was selected and cut into a rectangular sheet with a length of 4 cm and a width of 2 cm, and clamped on a glassy carbon electrode clamp. The specific clamping method is shown in Figure 1 b.
[0051] Clamping a length of about 1cm, immerse the 2cm*4cm graphene sample in the solution and clamp it on the negative electrode. The positive electrode is a carbon rod. Figure 1 a shows the overall electrochemical intercalation circuit and device diagram. At a constant voltage of -5 V, the sample was clamped at the negative electrode and the reaction time was 20 minutes. Figure 1 b shows the clamping method and immersion area of the sheet-like bulk two-dimensional material. Figure 1 c shows the material changes before and after electrochemical intercalation, where the intercalated molecules can be seen entering the interlayers of the two-dimensional material. After the reaction is completed, the two-dimensional material is removed and dried naturally at room temperature to obtain a high-temperature ferromagnetic material of the graphene-pyridine system.
[0052] By replacing the pyrline molecules with 7,7,8,8-tetracyanoquinodimethane (TCNQ), naphthoquinone (NTO), hydroquinone (Hy), etc., high-temperature ferromagnetic materials of graphene-7,7,8,8-tetracyanoquinodimethane system, high-temperature ferromagnetic materials of graphene-naphthoquinone system and high-temperature ferromagnetic materials of graphene-hydroquinone system are prepared respectively.
[0053] In addition, by replacing graphene with transition metal disulfides represented by molybdenum disulfide, due to the difference in interlayer van der Waals forces between different two-dimensional materials, the solution concentration is increased, the constant voltage is increased, and the reaction time is increased according to the difference in interlayer van der Waals forces. According to similar methods, high-temperature ferromagnetic materials of molybdenum disulfide-pyridine system, high-temperature ferromagnetic materials of molybdenum disulfide-7,7,8,8-tetracyanoquinone dimethane system, high-temperature ferromagnetic materials of molybdenum disulfide-naphthoquinone system, and high-temperature ferromagnetic materials of molybdenum disulfide-hydroquinone system can be prepared.
[0054] In addition, the degree of electrochemical intercalation of high-temperature ferromagnetic materials can be adjusted by solutions of different proportions, such as preparing molecular organic solutions with concentrations of 1 mg / mL, 2 mg / mL, 5 mg / mL, 10 mg / mL and 20 mg / mL. Since magnetism is derived from the number of inserted molecules, in the concentration selection, at low concentrations, magnetism will increase with the increase of concentration, while in the high concentration range, too many molecules will further destroy the original state of the sample. Therefore, in order to ensure high magnetism and sample integrity, taking the graphene system as an example, a solution concentration of 5 mg / mL was selected, while the common solution concentration of transition metal disulfide systems such as molybdenum disulfide is 10 mg / mL.
[0055] The magnetic test (SQUID VSM, Quantum Design, USA) based on the metal-free high-temperature ferromagnetic material of the present invention was carried out under the magnetic field of plus or minus 7T and the temperature conditions of 2 Kelvin and 300 Kelvin. Figure 3 As shown in a, the graphene-pyridine system saturates at 1 T and exhibits strong magnetocrystalline anisotropy. The in-plane / out-of-plane hysteresis loop shows that the easy magnetization axis of the material is in the plane.
[0056] Figure 3 b and 3c show the good magnetic saturation and high environmental stability of the material. In the range from low temperature to room temperature, the magnetic saturation intensity of the material changes very little with temperature. From the zero field cooling curve (ZFC, square solid line) and the field cooling curve (FC, circle solid line) in Figure c, both decrease to 0 at about 900K, it can be seen that the Curie temperature of the material is as high as 900K. Figure 3 In d, by comparing the free radical magnetic materials (squares) and inorganic non-metallic materials (circles) reported in the literature, the high temperature ferromagnetic material (star) of the present invention not only has a higher saturation magnetic susceptibility than other metal-free organic / molecular materials (see Table 1 for specific performance comparison), but also has a Curie temperature (which also represents high temperature stability) much higher than other materials. Moreover, the material still has 60% of the initial performance after being stored for half a year under room temperature and normal humidity environment, showing good magnetic saturation and high environmental stability.
[0057] Table 1
[0058]
[0059]
[0060] Table 2 and Figure 4 The extended extensibility of metal-free high-temperature ferromagnetic materials was demonstrated. Graphene and molybdenum disulfide were extended in two-dimensional materials, and pyridine, 7,7,8,8-tetracyanoquinodimethane (TCNQ), naphthoquinone (NTO), hydroquinone, etc. were extended in molecules. The various materials had different carrier concentrations (at 2K, the graphene-pyridine system was 6.78G10 23 cm -3 , graphene-TCNQ system is 2.49G 10 23 cm -3 , graphene-NTO system is 5.0G 10 22 cm -3 ) shows a relatively linear difference in magnetic saturation. Figure 5 Demonstrated negative magnetoresistance of graphene-pyridine system ( Figure 5 a) and anomalous Hall effect ( Figure 5 b) (In the Quantum Design comprehensive physical property test system, the Hall device was measured using SR830, Stanford's lock-in amplifier, where the magnetic field range is ±2T), and the negative magnetoresistance value still remains at -4.8% at room temperature; in addition, graphene-TCNQ still has -0.8% at room temperature, and graphene-NTO still has -0.3%. )
[0061] Table 2
[0062]
[0063]
[0064] Example 2 is a method for preparing a Hall device based on metal-free high-temperature ferromagnetic materials.
[0065] The present invention also provides a Hall device based on metal-free high-temperature ferromagnetic materials, by Figure 2 The Hall device is prepared by the preparation method shown, and includes a substrate silicon wafer, a titanium-gold eight-claw electrode, a two-dimensional organic molecular orbital coupling material and an aluminum-silicon alloy wire; wherein, the substrate silicon wafer has an oxide layer, the two-dimensional organic molecular orbital coupling material is transferred to the silicon wafer oxide layer by hand-tearing, the titanium-gold eight-claw electrode is evaporated and attached to the material and the substrate silicon wafer to form a Hall device, and the aluminum-silicon alloy wire is used to connect the eight-claw electrode to an external circuit.
[0066] In this embodiment, the oxide layer is made of silicon oxide. The external circuit includes a connected digital source meter. In this embodiment, the substrate silicon wafer is a square with a side length of 2.5 cm; the length of the aluminum silicon alloy wire 5 is 1-3 cm.
[0067] The preparation method specifically comprises:
[0068] S100: preparing a silicon wafer containing an oxide layer into a silicon wafer with eight-claw electrodes attached thereto, specifically comprising:
[0069] An eight-claw electrode pattern is masked on a silicon wafer containing an oxide layer by ultraviolet lithography, and metal titanium and metal gold are sequentially evaporated on the silicon wafer by electron beam evaporation, wherein the metal titanium serves as an adhesion layer and the metal gold serves as an electrode material; the evaporated silicon wafer is immersed in acetone and ultrasonically treated to remove the metal layer outside the eight-claw electrode area, and the silicon wafer with the eight-claw electrode is rinsed with acetone and isopropanol successively, and blown dry with high-purity nitrogen to obtain a silicon wafer with eight-claw electrodes attached;
[0070] S200: Transferring two-dimensional materials of appropriate thickness to the appropriate position on the silicon wafer by mechanical peeling with blue tape (UltraType), including:
[0071] The silicon wafer with the eight-claw electrode obtained in step S100 is placed in a plasma generator and cleaned with oxygen plasma, and then heated;
[0072] The two-dimensional material is transferred to the PDMS through the blue tape (UltraType) mechanical glass to obtain the appropriate thickness, and then the appropriate two-dimensional material sample is transferred from the PDMS to the appropriate position of the silicon wafer using the transfer platform;
[0073] S300: Spin-coat PMMA on the silicon wafer in step S200 through a spin coater, heat it at a suitable temperature for a period of time, expose a suitable single electrode pattern on the silicon wafer through an electron beam exposure process, and evaporate metal titanium and metal gold on the silicon wafer using electron beam evaporation.
[0074] S400: The silicon wafer after evaporation in step S300 is placed in acetone for immersion and ultrasonic treatment to remove the metal layer outside the eight-claw electrode area, and an appropriate window is exposed near the sample by electron beam exposure process. An electrochemical three-electrode system is used, a carbon rod is used as a counter electrode, and Ag / AgCl is used as a reference electrode. An electrochemical intercalation reaction is carried out in a reaction chamber prepared by PDMS material. The solution is 5 mg mL -1 Pyridine / DMSO solution, set the constant voltage to -5V, and apply the voltage for 20 minutes.
[0075] S500: After the silicon wafer after the intercalation in step S400 is placed in acetone and soaked to remove the extra PMMA, the PMMA is re-spin-coated by a spin coater, and after heating at a suitable temperature (170 degrees, 10 minutes), an additional Hall electrode pattern is exposed on the silicon wafer by an electron beam exposure process, and metal titanium and metal gold are evaporated on the silicon wafer by electron beam evaporation;
[0076] S600: After the silicon wafer after the vapor deposition in step S500 is immersed in acetone to remove the extra PMMA, a Hall device based on metal-free high-temperature ferromagnetic material is prepared.
[0077] The present invention also provides an application of a Hall device based on a metal-free high-temperature ferromagnetic material in negative magnetoresistance and anomalous Hall.
[0078] The working principle is: through an external Hall test device, a Hall six-electrode device of a two-dimensional organic molecular orbital coupling material applies a constant current through the source and drain on both sides, and at the same time detects V at the two electrodes on the inner side. xx The lateral voltage is detected by the two electrodes corresponding to the longitudinal direction. XY The longitudinal Hall voltage is divided by the applied constant current to obtain the magnetic resistance R XX With Hall resistance R XY When a changing magnetic field is applied, the magnetic resistance R XX With Hall resistance R XY The trend curve of the change relative to the magnetic field. This can further develop the application of Hall devices and magnetoresistance effect for carrier regulation of two-dimensional materials.
[0079] The present invention provides a two-dimensional organic molecular orbital coupling material obtained by electrochemically intercalating pyrline into graphene interlayers, realizing the phenomenon of negative magnetic resistance under a magnetic field and the anomalous Hall effect, thereby proposing a new extension to the field of spin electronics.
[0080] The present invention uses two-dimensional materials as substrates, and obtains two-dimensional organic molecular orbital coupling materials by electrochemically inserting organic molecules between two-dimensional material layers, thereby realizing metal-free high Curie temperature ferromagnetic materials, and realizing room temperature anomalous Hall and magnetoresistance effects by preparing devices. The synthesis method of the present invention is green and simple, and the preparation of Hall devices is simple. A series of two-dimensional molecular orbital coupling magnetic materials of different molecules / two-dimensional materials can be synthesized, which extends new development to organic / metal-free spin electronic devices and magnetoresistance devices.
[0081] The parts not involved in the present invention are the same as the prior art or are implemented by the prior art. The above content is a further detailed description of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A metal-free high-temperature ferromagnetic material, characterized in that: The high-temperature magnetic material is obtained by inserting organic free radical molecules into the interlayer of a two-dimensional material using an electrochemical intercalation method, wherein the organic free radical molecules are any one or more of pyridine, 7,7,8,8-tetracyanoquinone dimethane, naphthoquinone, and hydroquinone, and the two-dimensional material is graphene or a transition metal disulfide represented by molybdenum disulfide.
2. The method for preparing the metal-free high-temperature ferromagnetic material according to claim 1, characterized in that: The steps include: A100: Dissolve certain organic free radical molecules in a solvent and dissolve them by ultrasonic to obtain a molecular organic solution; A200: clamping a sheet-like block of two-dimensional material with a fixture; A300: partially immersing the clamped two-dimensional material in the molecular organic solution, and connecting the two-dimensional material and a suitable counter electrode respectively with two electrodes; A400: Electrochemically intercalate the two materials for a certain period of time using a suitable constant voltage to obtain a two-dimensional molecular orbital coupled magnetic material, i.e., a high-temperature ferromagnetic material.
3. The method according to claim 2, characterized in that In step A100, the solvent is any one of dimethyl sulfoxide, dimethylformamide, isopropanol, cyclohexane, acetone, and acetonitrile; and the molecular concentration range of the molecular organic solution is 5 mg / mL to 20 mg / mL.
4. The method according to claim 2, characterized in that: In step A200, the thickness of the sheet-like block two-dimensional material ranges from 0.1 mm to 0.5 mm, the length and width range from 2 cm to 4 cm, and the area ranges from 2 cm 2 ~ 8cm 2 .
5. The method according to claim 2, characterized in that: In step A400, the conditions for electrochemical intercalation are: a constant voltage range of -5V to -20V, a reaction time of 10min to 1h, and after the reaction is completed, the two-dimensional material is taken out and dried naturally.
6. Use of the high temperature ferromagnetic material according to claim 1 in the preparation of devices.
7. A magnetic device, characterized in that: The Hall device includes a substrate silicon wafer, a titanium eight-claw electrode, the high-temperature ferromagnetic material according to claim 1, and an aluminum-silicon alloy wire, wherein the substrate silicon wafer has an oxide layer, the high-temperature ferromagnetic material is transferred to the oxide layer by a mechanical stripping method, the titanium eight-claw electrode is evaporated and attached to the high-temperature ferromagnetic material and the substrate silicon wafer to form a magnetic device, and the aluminum-silicon alloy wire is used to connect the titanium eight-claw electrode to an external circuit; the oxide layer is silicon oxide, the external circuit includes a digital source meter, the substrate silicon wafer is a square with a side length of 2.5 cm; the length of the aluminum-silicon alloy wire is 1-3 cm.
8. The method for preparing a magnetic device according to claim 7, characterized in that: The steps include: (1) Preparing a silicon wafer containing an oxide layer into a silicon wafer with eight-prong electrodes attached thereto: masking an eight-prong electrode pattern on the silicon wafer containing an oxide layer by ultraviolet lithography, and sequentially evaporating metal titanium and metal gold on the silicon wafer by electron beam evaporation, wherein the metal titanium serves as an adhesion layer and the metal gold serves as an electrode material; soaking the evaporated silicon wafer in acetone and ultrasonically treating it to remove the metal layer outside the eight-prong electrode area, and then rinsing the silicon wafer with the eight-prong electrodes with acetone and isopropanol in turn, and drying it with high-purity nitrogen to obtain a silicon wafer with eight-prong electrodes attached thereto; (2) Transferring the two-dimensional material of appropriate thickness to a suitable position on the silicon wafer by using a blue tape mechanical peeling method, specifically including: The silicon wafer with the eight-claw electrode obtained in step S100 is placed in a plasma generator and cleaned with oxygen plasma, and then heated; The two-dimensional material is mechanically peeled off with blue tape to obtain a suitable thickness, and then transferred to the PDMS polydimethylsiloxane film. Subsequently, the two-dimensional material sample is transferred from the PDMS to the appropriate position of the silicon wafer using a transfer platform; (3) Spin-coating the silicon wafer obtained in step (2) with PMMA polymethyl methacrylate by a spin coater, heating for a period of time, exposing a suitable single electrode pattern on the silicon wafer by an electron beam exposure process, and evaporating metal titanium and metal gold on the silicon wafer by electron beam evaporation; (4) soaking the evaporated silicon wafer obtained in step (3) in acetone and ultrasonically treating the silicon wafer to remove the metal layer outside the octagonal electrode area, exposing a suitable window near the sample by electron beam exposure, using an electrochemical three-electrode system, using a carbon rod as a counter electrode and Ag / AgCl as a reference electrode, and performing an electrochemical intercalation reaction in a reaction chamber prepared by PDMS material; (5) After the intercalation in step (4), the silicon wafer is placed in acetone and soaked to remove the extra PMMA, and then PMMA is re-spin-coated using a spin coater. After heating at a suitable temperature, an additional Hall electrode pattern is exposed on the silicon wafer by an electron beam exposure process, and metal titanium and metal gold are evaporated on the silicon wafer by electron beam evaporation; (6) The evaporated silicon wafer obtained in step (5) is placed in acetone and soaked to remove the extra PMMA, thereby obtaining a magnetic device based on metal-free high-temperature ferromagnetic material.
9. Application of the magnetic device according to claim 7 in negative magnetoresistance and anomalous Hall.
Citation Information
Patent Citations
Two-dimensional material-organic ferromagnetic material superlattice storage unit and fabrication thereof
CN108878429A
Two-dimensional material-organic ferromagnetic material superlattice storage unit and fabrication thereof
CN108878642A
Preparation method and application of organic-inorganic heterojunction
CN111430540A
Two-dimensional composite material, preparation method and application thereof
CN112777585A
Layered quantum magnetic material and preparation method thereof
CN115583637A
